UTILIZATION OF THE JKN MOBILE APPLICATION AS AN EFFORT TO SUPPORT PAPERLESS IN SAMARINDA CITY - -, Apriyani; Wulandari, Kartina; -, Suwignyo; Kusumawati, Rindha Mareta (Indonesian Journal for Health Sciences, 2024)
One of the efforts to support paperless is using various media, including the JKN mobile application (National Health Guarantee). Health BPJS continues to work on expanding the participation coverage to reach all citizens and encourage them to become JKN-KIS participants. JKN Mobile Application is an innovation by Health BPJS to improve the community's service in the health field. Through the run of this application, it can be seen whether JKN mobile application usage has been utilized. The purpose of this research was to find out the utilization of JKN mobile application usage. The analysis method used was descriptive quantitative analysis. The research respondents used the JKN mobile application, which comprised 27 people (28,13%). At the same time, those who did not use the JKN mobile application were 69 people (71,88%). Based on those data, it could be concluded that the usage level of JKN mobile application in research respondents was 28,13%. At the same time, the application can give various benefits to JKN participants.